PENYESATAN SESAMA KELOMPOK ISLAM: SEBUAH PROBLEM MENJADI MANUSIA BERADAB - Nur Khalik Ridwan (Millah: Journal of Religious Studies, 2008)
The rising of the religious sects that are claimed as deviant and kafir has been a controversial issue today. This paper dedicates to review the phenomenon, both from the basic of Muslim’s faith and from the historical context. Based on those perspectives, this article will analyzes the phenomenon of the religious sects vis a vis mainstream groups of Islam. This phenomenon can be resumed into two perspectives; first, the sects which are claimed as deviant can be categorized as madzhab in Islam. Secon, that sects can also be indicated as new religion. From the mainstream Muslim group side, the sects was delayed both as madzhab of Islam and also new religion, because they believe that there is no true religion but Islam. Therefore, all these sects will be refused and should be destroyed. Here, the Muslims are not able to make the norms of living together and harmony. In fact, Islam indeed teachs freedom of speech, thought, and faith. Every one can choose anything without any pressure. To over come their daily problems, they have to have sense of humanity and non-violence attitudes.